Do leaf-cutter ants Atta colombica obtain their magnetic sensors from soil? (2013)
How animals sense, process, and use magnetic information remains elusive. In insects, magnetic particles are candidates for a magnetic sensor. Recent studies suggest that the ant Pachycondyla marginata incorporates iron-containing particles from soil. We used leaf-cutter ants Atta colombica to test whether soil contact is necessary for developing a functional magnetic compass. A. colombica is the only invertebrate known to calculate a path-integrated home vector using a magnetic compass. Here, we show that A. colombica requires contact with soil to incorporate magnetic particles that can be used as a magnetic compass; yet, we also show that ants can biosynthesize magnetic particles. Workers from a soil-free colony ignored a 90° shift in the horizontal component of the geomagnetic field, yet oriented homeward despite the occlusion of any geocentric cues. In contrast, workers from a soil-exposed colony oriented to an intermediate direction between their true and subjective home in the shifted field. Homeward orientations under shifted fields suggest that ants calculated a path-integrated vector using proprioceptive information. Strikingly, ants from the soil-free colony also had magnetic particles; yet, as observed by ferromagnetic resonance, these particles differed from those in soil-exposed ants and were not associated with a magnetic compass sensitive to this experimental manipulation.